THE INFLUENCE OF SCHOOL-BASED MANAGEMENT ON THE QUALITY OF IMPLEMENTATION OF MANDARIN LANGUAGE LEARNING - Annisa, Anni; Maulida, Maulida; Insiyah, Cici’; Hasanah, Uswatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the influence of school-based management on the quality of the implementation of Mandarin language learning at Mambaul Ulum Bata-bata Putri Middle School and how much influence school-based management has on the quality of the implementation of Mandarin language learning at Mambaul Ulum Bata-bata Putri Middle School. This research method used a quantitative approach, the population of this study were all teachers at SMP Mambaul Ulum Bata-bata Putri, namely 11 teachers, considering that the total population was less than 100, the researchers took all teachers at SMP Mambaul Ulum Bata-bata Putri. The instruments used in data collection are questionnaires, observation, and documentation. The data analysis technique used is product moment statistical analysis. The results showed that first, there was no significant influence between school-based management on the quality of the implementation of Mandarin language learning at SMP Mambaul Ulum Bata-bata Putri by comparing the amount of work obtained in the calculation (r work 0.021 and the amount of r table 5% 0.666 and the amount of r table 1% 0.798) then we know that r work is smaller than r table namely: (0.666> 0.021 <0.798). secondly by calculating (ʳxy=0.021 and 5% interval 0.666, 1% 0.798) it can be seen that r work is smaller than r table (0.666>0.021<0.798) so the effect of school-based management on the quality of the implementation of Mandarin language learning in junior high school Mambaul Ulum Bata-bata Putri is classified as very low